The Relationship Between Emotional Intelligence and Psychological Well-Being Among the Inmates of LPP Class IIA Martapura - Selvianti; Rizqi Amalia; Dyta Setiawati H (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Psychological well-being is the realization of the full achievement of individual potential where individuals can accept all their shortcomings and strengths, are independent, are able to foster positive relationships with others, can master their environment in the sense of being able to modify the environment to suit their wishes, have life goals, and continue to develop their personality. WBP who are in prison will experience many changes both physically and psychologically often feel fear, anxiety, and inability to control themselves. The purpose of this study is to see the relationship between emotional intelligence and psychological well-being in LPP Class IIA Martapura Prisoners. The research method used is a quantitative method with a correlational design. This study used probability sampling technique with simple random sampling method, involving 100 WBP. The data analysis technique used, namely Pearson's Product's Moment correlation. The results showed a positive and significant correlation (r = 0.538 with p = 000). The findings of this study are that there is a relationship between emotional intelligence and psychological well-being in WBP. Where the higher the emotional intelligence in WBP, the higher the psychological well-being in WBP. And vice versa.